2016
DOI: 10.1002/hep.28838
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles released by hepatocytes from gastric infusion model of alcoholic liver disease contain a MicroRNA barcode that can be detected in blood

Abstract: Extracellular vesicles (EVs) released during cell stress, or demise, can contain a barcode of the cell origin including specific microRNAs (miRNAs). Here we tested the hypothesis that during early alcoholic steatohepatitis (ASH) development, hepatocytes (HCs) release EVs with a miRNA signature that can be measured in circulation. A time course experiment showed that after two weeks of intragastric infusion, a time-point that results in isolated steatosis, there was no increase of blood EVs. After four weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 39 publications
11
105
0
1
Order By: Relevance
“…Blockage of the CXCL1 receptor CXCR1/2 ameliorated alcoholic steatohepatitis in mice (14). In addition to chemokines, extracellular vesicles (EVs) are new players in cellto-cell communication and play an important role in promoting inflammation and neutrophil infiltration in a variety of diseases (15,16), including liver diseases (17)(18)(19)(20)(21)(22)(23)(24)(25). EVs are nanometer-sized, membrane-bound extracellular milieu vesicles derived from cells (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockage of the CXCL1 receptor CXCR1/2 ameliorated alcoholic steatohepatitis in mice (14). In addition to chemokines, extracellular vesicles (EVs) are new players in cellto-cell communication and play an important role in promoting inflammation and neutrophil infiltration in a variety of diseases (15,16), including liver diseases (17)(18)(19)(20)(21)(22)(23)(24)(25). EVs are nanometer-sized, membrane-bound extracellular milieu vesicles derived from cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of EVs are mediated by delivering their contents from one cell to another. For example, stressed hepatocytes can activate macrophages via the release of EVs that contain lipids, proteins, chemokines, and nucleic acids (e.g., mitochondrial DNA [mtDNA]) (17)(18)(19)(20)(21)(22)(23)(24)(25). However, whether EVs also contribute to the elevation of circulating and hepatic neutrophils induced by acute-on-chronic alcoholic liver injury in human and mice remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of pan-caspase inhibition on modulation of fibrogenic pathways, it has been recently shown to modulate the generation and release of hemodynamically-active microparticles (MPs) [17]. Indeed, MPs are small membrane-bound particles released from dying or activated cells in a process involving caspase 3 and Rho-associated kinase activation [4, 5]. Studies in patients with cirrhosis have demonstrated that MPs are increased in circulation of these patients and impair vasoconstrictor responses contributing to arterial vasodilatation associated with portal hypertension [6].…”
Section: Discussionmentioning
confidence: 99%
“…MPs are effective communicators that are generated by a cell of origin or parenteral cell and can act on a number of target cells in an autocrine or paracrine pathway in the extracellular environment where they are released, as well as in an endocrine manner, acting as long-range signals. Circulating MPs containing cytokeratin-18 and expressing phosphatidylserine on the surface are released by hepatocytes in a caspase dependent manner [4, 5] and have been shown to be increased in circulation of patients with cirrhosis, and in these patients to impair vasoconstrictor responses and decrease blood pressure [6], contributing to the arterial vasodilation that may represent an important contributor to the worsening of PHT. Broad-spectrum caspase inhibition via the use of pan-caspase inhibitors is a novel therapeutic approach that has been shown to have anti-inflammatory and anti-fibrotic effects in experimental models and in patients with chronic liver disease [710].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to intracellular localization, miRNAs are also detected in body fluids, such as urine, bile, saliva, serum and plasma, et al (Mitchell et al, 2008; Shigehara et al, 2011; Weber et al, 2010). Recent studies have suggested that circulating miRNAs are present in either the protein fraction or extracellular vesicles (Bala et al, 2012; Eguchi et al, 2017; Momen-Heravi, Saha, et al, 2015). The high stability of circulating miRNAs makes them attractive for biomarker discovery in liver diseases (Szabo & Bala, 2013).…”
Section: The Role Of Microrna In Inflammation Of Aldmentioning
confidence: 99%